The implementation of HIV/AIDS workplace programme in the Ministry of Education in Zambia - Chileshe, Patrick Shula (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.